2013
DOI: 10.1177/1538574413503560
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Radiocontrast Iodixanol Increases Permeability of Proximal Tubule Epithelium

Abstract: Our in vitro data do not support the hypothesis that direct kidney cell death from Iodixanol is a major mechanism of contrast-induced nephropathy (CIN). However, increased permeability of proximal tubule epithelium caused by Iodixanol may play an important role in CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Specifically, cell viability following exposure with CM at concentrations of 150, 225, and 300 mg I 2 /mL was 69.5%, 37.3%, and 4.8%. Such findings have been demonstrated on previously published HK2 models using similar MTT methods to assess cell viability [10,11,13]. Peng et al similarly identified a dose-dependent response with cell viability decreasing progressively from 100% to 12% following exposures of 80 mg I/ml over 16 hours [11].…”
Section: Zinc Preconditioning Has Protective Effect On Cell Viabilitysupporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, cell viability following exposure with CM at concentrations of 150, 225, and 300 mg I 2 /mL was 69.5%, 37.3%, and 4.8%. Such findings have been demonstrated on previously published HK2 models using similar MTT methods to assess cell viability [10,11,13]. Peng et al similarly identified a dose-dependent response with cell viability decreasing progressively from 100% to 12% following exposures of 80 mg I/ml over 16 hours [11].…”
Section: Zinc Preconditioning Has Protective Effect On Cell Viabilitysupporting
confidence: 58%
“…e cytotoxic effects of contrast on renal cells may have been effectively assessed in in vitro models. Specifically, several groups have outlined the reno-protective effects of various agents on HK-2 cell lines [7][8][9][10][11][12][13][14]. e aim of the current study is to assess the outcomes of zinc pre-conditioning on HK-2 renal cell lines following contrast administration.…”
Section: Introductionmentioning
confidence: 99%
“…Solute permeability was tested using 6.5 mm transwell inserts with 0.4 µm pore size (07–200-154, Fisher Scientific) as previously described [42] . Transwell inserts were coated with fibronectin.…”
Section: Methodsmentioning
confidence: 99%
“…Decreasing cell proliferation by CellTiter 96 assay. [ 53 ] LLC-PK1 (Pig renal tubular epithelial cells) Iodixanol (Visipaque) 18.75-75 mgI/ ml 24 h 1. Decreasing cell proliferation by BrdU assay 2.…”
Section: In-vitro Studies On Contrast-induced Nephropathy (Cmentioning
confidence: 99%